2012
DOI: 10.1680/geot.9.p.100
|View full text |Cite
|
Sign up to set email alerts
|

Small-strain behaviour of cemented soils

Abstract: The shear modulus of cemented soils at very small strain (G 0 ) was studied. For artificially cemented clay, G 0 was found to be independent of the mean effective stress until the yield stress. After yield, a significant effect of structure degradation on G 0 was observed. The experimental data were interpreted by an equation, which relates G 0 of cemented soils to mean stress, apparent overconsolidation ratio and the state of structure (sensitivity). The equation was also found to represent G 0 of cemented sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 26 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…In an investigation on the stiffness of cemented Bangkok clay, Piriyakul and Pochalard (2012) suggested that the replacement of fly ash in the range 15-20% at 20% cement content can achieve improved values of the undrained shear strength, shear wave velocity and initial shear modulus of stabilised soils compared with those of cemented soils with 0% fly ash replacement. Based on a study of the very-small-strain behaviour of cemented soils, Trhlíková et al (2012) concluded that the shear modulus of stabilised soils was controlled by cementation, and was independent of the mean effective stress until the yield stress was reached. After yielding, the shear modulus of cemented soils increases with an increase in the mean stress, but has a higher value compared with the uncemented soils.…”
Section: Introductionmentioning
confidence: 99%
“…In an investigation on the stiffness of cemented Bangkok clay, Piriyakul and Pochalard (2012) suggested that the replacement of fly ash in the range 15-20% at 20% cement content can achieve improved values of the undrained shear strength, shear wave velocity and initial shear modulus of stabilised soils compared with those of cemented soils with 0% fly ash replacement. Based on a study of the very-small-strain behaviour of cemented soils, Trhlíková et al (2012) concluded that the shear modulus of stabilised soils was controlled by cementation, and was independent of the mean effective stress until the yield stress was reached. After yielding, the shear modulus of cemented soils increases with an increase in the mean stress, but has a higher value compared with the uncemented soils.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 'l' and 'm' relate the effect of mean effective stress and overconsolidation ratio on Gmax respectively. In order to consider the effects of structure, Equation 1 was further modified into Equation 2 by Trhlíková et al [1], based on the framework proposed by Cafaro & Cotecchia [16] and Cotecchia & Chandler [25]:…”
Section: Methodsmentioning
confidence: 99%
“…Mixing soft clays with cement is a common practice for soil improvement as it results in imparting higher strength and reduced compressibility. Therefore, various studies investigating the influence of the structure due to cementation on small strain stiffness have been done [1][2][3][4][5]. A combination of bonding and fabric forms the basis for defining structure in clayey soils [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations